Tratado em que se contem muito susinta- e abreviadamente algumas contradicoes e derencas de custumes entre a gente de Europa e esta provincia de Japao. - Frois, Luis, -1597., author.
1 online resource (xi, 299 pages)
Keywords: "In 1585, at the height of the Jesuit missionary activity in Japan, which was begun by Francis Xavier in 1549, Luis Frois, a long-time missionary in Japan, drafted the earliest systematic comparison of Western and Japanese cultures. This book constitutes the first critical English-language edition of the 1585 work, the original of which was discovered in the Royal Academy of History in Madrid after the Second World War. The book provides a translation of the text, which is not a continuous narrative, but rather more than 600 distichs or brief couplets on subjects such as gender, child rearing, religion, medicine, eating, horses, writing, ships and seafaring, architecture, and music and drama. In addition, the book includes a substantive introduction and other editorial material to explain the background and also to make comparisons with present-day Japanese life. Overall, the book represents an important primary source for understanding a particularly challenging period of Japanese history and culture. "--